Evaluation of Luffa Rootstocks to Improve Resistance in Bitter Gourd (Momordica charantia L.) Against Fusarium Wilt - Ahmed Namisy; Shu-Yun Chen; Benjapon Sritongkam; Jintana Unartngam; Chinnapan Thanarut; Wen-Hsin Chung (Plants)
Fusarium wilt in bitter gourd caused by Fusarium oxysporum f. sp. momordicae (Fomo) is a severe plant disease that affects the world’s bitter gourd (Momordica charantia L.) cultivation. This study evaluated nine luffa hybrids for their performance as rootstocks with bitter gourd to control Fusarium oxysporum f. sp. luffae (Folu) isolate Fomh16 and Fomo isolate Fomo33. In the first evaluation, five hybrids (LF1, LF2, LF3, LF15, and LF16) exhibited resistance to the Fomh16 isolate and showed no symptoms. One hybrid, LF10, was resistant with a mean disease rating (MDR) of 0.9 at 28 days post-inoculation (dpi). Seven luff hybrids that displayed resistant and moderate resistance in the first evaluation were used as rootstocks with susceptible bitter gourd cultivars. Five rootstocks exhibited high resistance to Fomh16 and Fomo33 isolates, with their MDR ranging from 0.0 to 0.7. In addition, the findings revealed that both isolates could colonize the vascular bundle of all resistant luffa rootstocks at 28 dpi. However, the Fomo33 isolate could extend and colonize the vascular bundle of bitter gourd scion when grafted only with rootstock LF5 and LF11. The quantitative PCR results indicated that there were significant differences in the amount of the Fomo33 DNA between the bitter gourd grafted onto LF15 and LF16 rootstocks and the self-grafted plants; however, the pathogen cannot be detected in the bitter gourd scions grafted with resistant rootstocks. These findings provide valuable resistant sources that can be used as rootstocks to manage Fusarium wilt disease in bitter gourd.